Chondromyxoid fibroma of the distal fibula treated by percutaneous radiofrequency ablation. (19th July 2017) - Berenstein-Weyel, Tamar; Lebel, Ehud; Katz, Daniela; Applbaum, Yaakov; Peyser, Amos
Background: Percutaneous radiofrequency ablation (RFA) has been shown to be an effective treatment for soft tissue lesions and also benign bone tumors, especially osteoid osteoma. There are limited data regarding this technique in other bone tumors, specifically larger and more aggressive ones. Purposes: To describe the use of RFA as a definitive treatment and an alternative to traditional open surgery for the treatment of chondromyxoid fibroma (CMF), a benign but locally aggressive bone tumor. Case presentation: An 11.5-year-old girl was diagnosed with a 4-cm lytic bone lesion of the distal fibula. Evaluation, including biopsy, revealed CMF. It was managed by fluoroscopy-guided RFA only. Six-year follow-up demonstrated complete healing without damage to the adjacent distal fibular growth plate. Discussion and conclusions: RFA induces local heat in the ablation field and causes tissue necrosis. The depth of heat penetration and the size of heated sphere are accurately controlled by modern types of ablation probes and accurate positioning. The current report demonstrates the ability to use this percutaneous technique for larger and more aggressive bone tumors than has been indicated previously.